Antinociceptive activity of the novel RAGE inhibitor, papaverine, in a mouse model of chronic inflammatory pain. Issue 3 (2nd October 2020) - Yoshizawa, Kazumi; Takeuchi, Kota; Nakamura, Toka; Ukai, Saki; Takahashi, Yukino; Sato, Akira; Takasawa, Ryoko; Tanuma, Sei‐ichi
Abstract: Extracellular high‐mobility group box 1 (HMGB1) is known to mediate the inflammatory response through pattern recognition receptors, including the receptor for advanced glycation end products (RAGE) or the toll‐like receptors (TLRs). The aim of the present study was to investigate whether papaverine, a novel RAGE inhibitor, could suppress inflammatory pain in mice after several time points, which was induced by the injection of complete Freund's adjuvant (CFA). We also investigated the influence of redox modulation during a state of chronic inflammatory pain. Although papaverine did not suppress CFA‐induced mechanical allodynia on Day 7, papaverine significantly suppressed CFA‐induced mechanical allodynia on Days 14 and 28. In contrast, the radical scavenger N‐tert ‐Butyl‐α‐phenylnitrone (PBN) suppressed mechanical allodynia in mice on Days 7 and 14, but not on Day 28. We demonstrated that the RAGE inhibitor improves mechanical allodynia in chronic inflammatory conditions. Moreover, we also found that high levels of reactive oxygen species (ROS) contributed to the early phase of CFA‐induced mechanical allodynia. Precisely, lower ROS levels contributed to the inflammatory pain response via the all‐thiol HMGB1/RAGE signaling pathway during the chronic state. These findings led us to propose that ROS levels modulate RAGE and/or TLR4‐mediated inflammatory allodynia by regulating the concentrations of disulfide HMGB1 or all‐thiol HMGB1. Abstract : We found for the first time that the novel RAGE inhibitor papaverine exert an antinociceptive effect in chronic inflammatory conditions. Furthermore, these findings led us to propose that ROS levels modulate RAGE and/or TLR4‐mediated inflammatory allodynia by regulating the concentrations of disulfide HMGB1 or all‐thiol HMGB1.